Thermoresponsive PNIPAM-Grafted Silica Particles for Modulating Coffee-Ring Effects in Drying Colloidal Droplets - Seong Hwan Kim (2861699) (2025)
Thermoresponsive poly(N-isopropylacrylamide)-grafted silica (SiO2-PNIPAM) particles were synthesized to control the drying patterns of colloidal suspension droplets. These particles undergo a hydrophilic-to-hydrophobic transition at a lower critical solution temperature (LCST) of ∼34 °C in water. Below the LCST, the SiO2-PNIPAM particles follow the outward capillary flow and accumulate at the edge. Above the LCST, surface tension gradients arising from temperature and concentration differences induce inward interfacial flow, redistributing the particles toward the center and suppressing coffee-ring formation. In mixed suspensions of SiO2 and SiO2-PNIPAM particles, when the SiO2-PNIPAM content exceeds 50%, the induced interfacial flow is sufficiently strong to drive unmodified SiO2 particles toward the droplet interior, enabling uniform particle deposition. At lower SiO2-PNIPAM contents, heteroaggregation between SiO2 and SiO2-PNIPAM particles results in disordered patterns. This study exploits tunable interfacial behaviors of functional particles to partially incorporate them into conventional colloidal systems, demonstrating a simple, cost-effective strategy for mitigating inhomogeneous drying patterns.